AUTOMOTIVE SEAT DESIGN: BASIC ASPECTS (Asian Journal of Current Engineering and Maths, 2015)
Overall seating comfort is influenced by both static and dynamic characteristics of seat system. For occupantâ€™s comfort and health, good seat design should be applied by considering sitting postures. Static and dynamic anthropometry data are considered for proper design of a comfortable and safe seat. Seats are one of the most important components of vehicles and they are the place where professional driver spend most of their time. For example, according to Occupational Outlook Handbook by United State Department of Labor, the truck drivers frequently work 50 or more hours a week. The truck drivers sit while they are driving their 50 hours per week. Assuming four weeks vacation and one more for holidays, which is about 2350 hours driving time per year. Automotive seats, which are in contact with vehicle occupants, play an important role in improving the comfort and work environment of a driver and passengers. The improvement of automotive seating systems, particularly for the driver, has been the subject of intense interest for many years since a driver feels more fatigue than passengers. The paper describes some case studies and up-to-date techniques developed for vehicle seats that used by different type of transportation system such as cars, trucks, tractors, trains etc. The objective of this paper is to review the state of the art of vehicle seat design.Â